A Novel Systems Pharmacology Method to Investigate Molecular Mechanisms of Scutellaria barbata D. Don for Non-small Cell Lung Cancer - Liu, Jianling; Jiang, Meng; Li, Zhihua; Zhang, Xia; Li, XiaoGang; Hao, Yuanyuan; Su, Xing; Zhu, Jinglin; Zheng, Chunli; Xiao, Wei; Wang, Yonghua (Frontiers in Pharmacology, 2018)
Non-small cell lung cancer (NSCLC) is the most ordinary type of lung cancer which leads to 1/3 of all cancer deaths. At present, the cytotoxic chemotherapy, surgical resection, radiation and photodynamic therapy are the main strategies for NSCLC treatment. However, NSCLC are relatively resistant to the above therapeutic strategies, resulting in a rather low (20%) 5-year survival rate. Therefore, there is an urgent need to identify or develop efficient lead compounds for the treatment of NSCLC. Here, we report that the herb Scutellaria barbata D.Don (SBD) can effectively treat NSCLC by anti-inflammatory, promoting apoptosis, cell cycle arrest and angiogenesis. In this work, we analyze the molecular mechanism of SBD for NSCLC treatment by applying the systems pharmacology strategy. This method combines the pharmacokinetics analysis with pharmacodynamics evaluation to screen out the active compounds, predict the targets and assess the networks and pathways. Results show that 33 compounds were identified with potential anti-cancer effects. Utilizing these active compounds as probes, we predicted that 145 NSCLC related targets main involved four aspects: apoptosis, inflammation, cell cycle and angiogenesis. And in vitro experiments were managed to evaluate the reliability of some vital active compounds and targets. Overall, a complete overview of the integrated systems pharmacology method provides a precise probe to clarify the molecular mechanisms of SBD for NSCLC. Moreover, baicalein from SBD effectively inhibited tumour growth in an LLC tumor-beaing mice models, demonstrating the anti-tumour effects of SBD. Our findings further provided experimental evidence for the application in the treatment of NSCLC.